Virtual Reality for Traumatic Brain Injury - Zanier, Elisa R.; Zoerle, Tommaso; Di Lernia, Daniele; Riva, Giuseppe (Frontiers in Neurology, 2018)
In this perspective, we discuss the potential of virtual reality (VR) in the assessment and rehabilitation of traumatic brain injury (TBI), a silent epidemic of extremely high burden and no pharmacological therapy available. VR, endorsed by the mobile and gaming industries, is now available in more usable and cheaper tools allowing its therapeutic engagement both at the bedside and during the daily life at chronic stages after injury with terrific potential for a longitudinal disease modifying effect.